Identity, Motivation and Autonomy in Language Learning - Ashurova, Umida; Ssali, Vick L. (Innovation in Language Learning and Teaching, 2015)
Autonomous (or independent) learning is still a hot area in current studies and research in language learning. More traditionally defined as ‘the ability to take charge of one’s own learning’ (Holec 1981, 3), the concept of autonomy also stands out as the starting point for talking about self-access language learning and all other language learning and teaching settings outside the traditional classroom.
Keywords: motivation; autonomy; language learning